Current situation and trend of non-coding RNA in rheumatoid arthritis: a review and bibliometric analysis - Wei, Zehong; Li, Huaiyu; Lv, Senhao; Yang, Junping (Frontiers in Immunology, 2024)
Background: Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease that affects multiple joints and has adverse effects on various organs throughout the body, often leading to a poor prognosis. Recent studies have shown significant progress in the research of non-coding RNAs (ncRNAs) in RA. Therefore, this study aims to comprehensively assess the current status and research trends of ncRNAs in RA through a bibliometric analysis. Methods: This study retrieved articles relevant to ncRNAs and RA from the Science Citation Index Expanded Database of the Web of Science Core Collection between January 1st, 2003, and July 31st, 2023. The relevant articles were screened based on the inclusion criteria. VOSviewer and CiteSpace are utilized for bibliometric and visual analysis. Results: A total of 1697 publications were included in this study, and there was a noticeable increase in annual publications from January 1st, 2003, to July 31st, 2023. China, the United States, and the United Kingdom were the most productive countries in this field, contributing to 43.81%, 13.09%, and 3.87% of the publications. Anhui Medical University and Lu Qianjin were identified as the most influential institution and author. Frontiers In Immunology stood out as the most prolific journal, while Arthritis & Rheumatology was the most co-cited journal. Additionally, the research related to "circular RNA", "oxidative stress", "proliferation", and "migration" have emerged as new hotspots in the field.In this study, we have summarized the publication characteristics related to ncRNA and RA and identified the most productive countries, institutions, authors, journals, hot topics, and trends. [17]), to visually analyze the publications related to ncRNAs in RA, and identify the global research status, trends, and hotspots in the field.In this study, we retrieved and downloaded the data from the Science Citation Index Expanded (SCI-Expanded) Database of the Web of Science Core Collection (WoSCC) on August 20, 2023. The procedure for data retrieval and collection is illustrated in Fig. 1. The search strategy was as follows: TS=(("rheumatoid arthritis") AND ("non-coding RNA" OR "noncoding RNA